Color and Brightness Tuning in Heteronuclear Lanthanide Terephthalate Coordination Polymers. Issue 20 (7th June 2013) - Haquin, Victor; Etienne, Mael; Daiguebonne, Carole; Freslon, Stéphane; Calvez, Guillaume; Bernot, Kevin; Le Pollès, Laurent; Ashbrook, Sharon E.; Mitchell, Martin R.; Bünzli, Jean‐Claude; Eliseeva, Svetlana V.; Guillou, Olivier
Abstract: Heteronuclear lanthanide terephthalate coordination polymers with the general chemical formula [Ln2–2 x Ln′2 x (bdc)3 (H2 O)4 ]∞, for which bdc 2– symbolizes benzene‐1, 4‐dicarboxylate (or terephthalate) and Ln and Ln′ represent trivalent rare earth ions, were synthesized and structurally characterized. Analysis of the Y/Lu compounds by 89 Y and 13 C solid‐state NMR spectroscopy was carried out, and the results support the hypothesis of randomly distributed lanthanide ions. The spectroscopic and colorimetric properties of this family of compounds were investigated in detail. The resulting data demonstrate that this series of compounds presents highly tunable luminescence properties and clearly indicate that intermetallic deactivation processes play an important role in the emission mechanism. Playing with intermetallic distances allows one to tune the color and the brightness of the lanthanide emission in these coordination polymers. Abstract : Heteronuclear lanthanide coordination polymers are synthesized and characterized. Solid‐state NMR spectroscopy confirms the hypothesis of randomly distributed lanthanide ions. The spectroscopic and colorimetric properties are investigated. The resulting data demonstrates that this series of compounds presents highly tunable luminescence properties.